A new genus of capillariids from birds, Ornithocapillaria gen. n. (Nematoda: Capillariidae) - Barus, V; Sergeeva, T P (Folia parasitologica, 1990)
A new genus, Ornithocapillaria gen. n., belonging to the family Capillariidae and subfamily Baruscapillariinae is described and its diagnosis is given. The type species of the genus is Ornithocapillaria ovopunctata (Linstow, 1873) comb. n., other species are O. cylindrica (Eberth, 1863) comb. n., O. quiscali (Read, 1949) comb. n., and O. picorum (Rudolphi, 1819) comb. n. The new genus is characterized by a relatively large membranous pseudobursa, shape of processes supporting pseudobursa, and presence of a vulval appendage in female. It includes only species parasitic in the intestine of birds of the orders Passeriformes, Falconiformes, Strigiformes, and Piciformes.
Keywords: nemoci ptáků; Female; Nematoda; hlístice; Animals; Nematode Infections; ptáci; ženské pohlaví; Bird Diseases; mužské pohlaví; Birds; Intestinal Diseases, Parasitic; Male; zvířata; parazitární nemoci střev; nematodózy